Optimal defense strategies against intelligent cyber attacks - Ertem, Mehmet; Bier, Vicki M. (İdris Karagöz, 2024)
We propose a comprehensive game-theoretic model pertaining to the security of computer networks, specifically addressing the interaction between defenders and attackers. The model incorporates attack graphs to outline potential attacker strategies and defender responses. To account for the attacker's capacity to execute multiple attempts, we introduce a probabilistic element, wherein the success or failure at any arc of the attack graph is treated as stochastic. This characterization gives rise to a multi-stage stochastic network-interdiction problem. In this problem formulation, the defender strategically interdicts a set of arcs in anticipation of the likely actions of the attacker, who, in turn, can make multiple attempts to traverse the network. We mathematically articulate this scenario as a stochastic bilevel mixed-integer program with a "min-max" objective. The defender's aim is to minimize the probability of the attacker's success, while the attacker seeks to maximize the probability of successfully traversing the network across multiple attempts. The defender's stochastic bilevel optimization model is solved using the integer L-shaped method. Upon analyzing the defender's perspective, we observe the anticipated trend that the overall success probability of the attacker diminishes with an increasing level of defense. Notably, in the sensitivity analysis involving relatively small attack graphs, we discover that the optimal defense strategy against a myopic attacker often aligns with that against a non-myopic attacker. Furthermore, in instances where deviations exist, the disparity in performance is generally marginal. However, our findings demonstrate a potential divergence in optimal defense strategies when the available attack paths share numerous common arcs.

Bilgisayar ağlarının güvenliği ile ilgili olarak, savunucular ve saldırganlar arasındaki etkileşimi özellikle ele alan kapsamlı bir oyun teorisi modeli öneriyoruz. Model, potansiyel saldırgan stratejilerini ve savunucu tepkilerini belirlemek için saldırı grafiklerini içermektedir. Saldırganın birden çok girişimi gerçekleştirme kapasitesini hesaba katmak için başarılı veya başarısız olma olasılığını herhangi bir saldırı grafiği yayında stokastik olarak ele alan bir olasılıksal öğe tanıtıyoruz. Bu karakterizasyon, çok aşamalı stokastik bir ağ-kesme problemine yol açmaktadır. Bu problem formulasyonunda, savunucu, saldırganın muhtemel eylemlerini önceden tahmin ederek bir dizi yayı engellemektedir. Ardından, saldırgan, ağı geçmeye yönelik birden çok girişimde bulunabilir. Bu senaryoyu matematiksel olarak, bir "min-max" hedefi olan stokastik bir iki seviyeli karma tamsayılı program olarak ifade ediyoruz. Savunucunun amacı, saldırganın başarısızlık olasılığını en aza indirmek iken, saldırgan, ağı birden çok girişimde başarıyla geçme olasılığını maksimize etmeye çalışmaktadır. Savunucunun stokastik iki seviyeli optimizasyon modeli, tamsayılı L-şekilli yöntem kullanılarak çözülmektedir. Savunucunun bakış açısını analiz ettiğimizde, saldırganın genel başarı olasılığının savunma seviyesinin artmasıyla azaldığı beklenen eğilimi gözlemliyoruz. Özellikle, göreceli olarak küçük saldırı grafiklerini içeren hassasiyet analizimizde, bir kör noktalı saldırgana karşı optimal savunma stratejisinin genellikle bir kör noktalı olmayan saldırgana karşı olanla uyumlu olduğunu keşfediyoruz. Ayrıca, sapmaların var olduğu durumlarda, performanstaki fark genellikle marjinaldir. Ancak, bulgularımız, mevcut saldırı yollarının birçok ortak yayı paylaştığı durumlarda optimal savunma stratejilerinde potansiyel bir ayrışma olduğunu göstermektedir.
Akıllı siber saldırılara karşı optimal savunma stratejileri
Keywords: System and Network Security; Sistem ve Ağ Güvenliği [EN] Multiple Criteria Decision Making; Çok Ölçütlü Karar Verme [EN] Stochastic (Probability ) Process; Stokastik (Olasılıksal) Süreçler